Floristične novosti z Notranjskega Snežnika - Wraber, Tone (Hladnikia (Ljubljana), 2004)
The research of the flora and vegetation of the Mt. Notranjski Snežnik (1796 m), the highest mountain of Slovenia outside the Alps, contributed also in theperiod after 1993 some floristic novelties worthy of notice. As new for theflora of Slovenia turned out Asperula beckiana and Euphrasia hirtella, which will be full discussed in other place. The finds ofArabis pumila subsp. stellulata, Omalotheca hoppeana, Potentilla brauniana, Sagina saginoides, Saxifraga exarata subsp. moschata and S. sedoides on the Mt. Snežnik are in Slovenia the first known localities discovered outside the Alps. These and others in the article treated taxa (Achillea clavennae var. intercedens f. velebitica, Arctostaphylos uva-ursi, Campanula cespitosa, Carex pilosa, Crocusvernus subsp. albiflorus, Orobanche reticulata, Pleurospermum austriacum, Potentilla caulescens, Rhamnus pumilus, Saxifraga paniculata, Serratula macrocephala, Streptopus amplexifolius) improve the knowledge of the floristicinventory of this phytogeographically and consequently for the conservation of nature interesting and important territory. The new localities, recorded in the upper region of the Mt. Snežnik (from the upper limit of the "subalpine" beech forest to the very top of the mountain), are situated in the quadrant 0452/2 of the Middle-Europe mapping grid.
Keywords: Classification; Ecosystem; Ekosistem; Plants; Rastline; Snežnik